Comparison Of The Clinical Presentation, Antimicrobial Properties, And Outcomes Of Lung And Disseminated Nocardiosis Patients (Journal of Pharmaceutical Negative Results, 2023)
Introduction: Nocardia are widely distributed in both water and soil. Nocardia is an infectious agent that spreads through injured skin and through respiratory exposure. Diseases of the lungs, skin, subcutaneous tissue, and extensive blood disorders may all be brought on by the organism. Chronic respiratory disease, immunosuppression brought on by steroid hormones or other immunosuppressants, HIV infection, solid organ transplants, and chemotherapy for malignancy are all prevalent risk indicators for Nocardia illnesses. Nocardiosis prevalence has risen in recent decades as a result of strong immunosuppressant drugs.Objectives: To compare the clinical presentation, antimicrobial properties, and outcomes of lung and disseminated nocardiosis patients.Methodology: Contributing diseases, participant types with pulmonary and widespread nocardiosis infections, immunosuppressants, the location of the Nocardia isolate, antibacterial treatment, surgical treatment, and the final outcome were all gathered. If blood cultures showed the existence of non-Nocardial microorganisms and the individual exhibited symptoms suggestive of bacteremia, the individual was said to have simultaneous bacteremia. Advancement in clinical signs and drug sensitivity measured in vitro were used to assess the efficacy of antibiotic treatment. Putative Nocardia species samples were placed on slides, treated with acid-fast dye using a modified procedure, and grown on agar media for at minimum two weeks to determine the existence of dominant Gram-positive filamentous microorganisms.Employing common biochemical tests for Nocardia, the isolates were classified down to the species identification. There were 18 participants in this research who had widespread nocardiosis with pulmonary disease. SPSS software version 25 was used for all data analysis. We evaluated the ratios using only a Chi-square test. It was deemed statistically relevant at a 0.05 p-value.Results:All of the sufferers, the most were male, had an average lifespan of 57.8 years. N. asteroides was primarily accountable for the human disease overall prevalence (44%) whereas N. brasiliensis was in charge of the majority of the disseminated instances (22%). The most prevalent underlying disease was chronic pulmonary disease, which contributed for 17% of occurrences. Cancer contributed for 12% of case scenarios.The form of therapy that was used the most frequently (28%) was the administration of a single medication. In contrast, participants with respiratory and disseminated nocardiosis were much more probable to have illnesses brought on by N. asteroides plus an underlying medical condition, such as malignancy or chronic pulmonary disease. These people also had clinically urgent conditions, such sepsis, and were frequently first given TB diagnoses when they didn't actually have the illness.Conclusion: Affected patients received combined antibacterial treatment and immunosuppression medications. Prior to performing a drug sensitivity test, it has been suggested that patients with respiratory or disseminated nocardiosis require standard treatment as an empirical treatment.